Social impacts of the mega events: An examination of Expo 2025 on residents’ well-being - Takatoshi Murayama; Graham Brown; Kohsuke Matsuoka (Societal Impacts)
This study examined host residents' perceptions of Expo 2025 that was held in Osaka, Japan. A survey of 1500 Osaka prefecture residents found that positive impacts of the event increased perceptions of subjective well-being, while perceptions of negative impacts decreased a sense of well-being. Well-being acted as a significant mediator between perceived event impact and residents’ support for the Expo. Positive beliefs about the recent Tokyo 2020 Olympics positively moderated attitudes about concerning the Expo. It is suggested that event organisers should communicate both tangible and intangible benefits to residents and to monitor any changes in residents’ well-being. This should be part of an internal marketing strategy that seeks to generate support among constituents, creating a virtuous cycle between mega-events and host communities. The finding of the moderating effect of the Tokyo 2020 Olympics is evidence of the value of an event portfolio strategy due to inter-event relationships.